2014
DOI: 10.5511/plantbiotechnology.14.0624a
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of mat rush lateral buds by air dehydration using aluminum cryo-plate

Abstract: A cryopreservation protocol based on air dehydration of explants placed on aluminium cryo-plates, termed D cryo-plate, was successfully developed for in vitro mat rush (Juncus decipiens Nakai) lateral buds. The buds of line 'Hiroshima 4gou(1)' with basal stems were dissected from multiple shoots and precultured overnight at 25°C on solid MS medium containing 0.3 M sucrose. Precultured buds were placed on aluminium cryo-plates, each one with 10 elliptical wells (2.5 mm long, 1.5 mm wide and 0.75 mm deep) and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 9 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…The D cryo-plate technique developed by Niino et al (2013Niino et al ( , 2014 was performed with some modifications (Matsumoto et al 2015). The cryo-plates ) used were obtained from the Genetic Resources Center, National Agriculture and Food Research Organization (Tsukuba, Japan).…”
Section: Cryopreservation Procedures For Shoot Tips Using the D Cryo-pmentioning
confidence: 99%
See 1 more Smart Citation
“…The D cryo-plate technique developed by Niino et al (2013Niino et al ( , 2014 was performed with some modifications (Matsumoto et al 2015). The cryo-plates ) used were obtained from the Genetic Resources Center, National Agriculture and Food Research Organization (Tsukuba, Japan).…”
Section: Cryopreservation Procedures For Shoot Tips Using the D Cryo-pmentioning
confidence: 99%
“…Recently, two novel cryogenic protocols using aluminum cryo-plates were developed, the osmo-dehydration method (V cryo-plate; Sekizawa et al 2011;Yamamoto et al 2011Yamamoto et al , 2012aYamamoto et al , 2012b and the air-dehydration method (D cryoplate; Niino et al 2013). The major advantages of the cryo-plate methods are their user-friendly procedures, minimization of shoot injury, and rapid cooling and warming, which results in higher recovery (Matsumoto et al 2015;Niino et al 2013Niino et al , 2014Salma et al 2014). Furthermore, the D cryo-plate method can be used with larger samples that are sensitive to physical damage and toxicity from certain cryoprotectants, such as PVS2 .…”
Section: Introductionmentioning
confidence: 99%
“…Niino et al (2014) indicated the need to avoid some shoot tips detaching themselves from the cryoplates during manipulations. The addition of 1 M glycerol and 0.4 M sucrose to the sodium alginate gel prevented the dropping of mat rush buds from the cryoplates .…”
Section: Modification Of the D Cryo-plate Protocol By Paper Mounting mentioning
confidence: 99%
“…1A1). The base D cryo-plate protocol was derived from the protocol developed by Niino et al (2014) and Yamamoto et al (2015) as follows: 1.…”
Section: Base D Cryo-plate Protocolmentioning
confidence: 99%
“…Excised shoot tips were cryopreserved using the D cryo-plate technique developed by Niino et al (2013Niino et al ( , 2014 with some modifications (Matsumoto et al, 2014a, b). The cryo-plates No.…”
Section: Cryopreservation Of Shoot Tips Using the D Cryo-plate Proceduresmentioning
confidence: 99%